Cognitive and affective perspective-taking in conduct-disordered children high and low on callous-unemotional traits - Anastassiou-Hadjicharalambous Xenia; Warden David (BMC, 2008)
Abstract Background Deficits in cognitive and/or affective perspective-taking have been implicated in Conduct-Disorder (CD), but empirical investigations produced equivocal results. Two factors may be implicated: (a) distinct deficits underlying the antisocial conduct of CD subgroups, (b) plausible disjunction between cognitive and affective perspective-taking with subgroups presenting either cognitive or affective-specific deficits. Method This study employed a second-order false-belief paradigm in which the cognitive perspective-taking questions tapped the character's thoughts and the affective perspective-taking questions tapped the emotions generated by these thoughts. Affective and cognitive perspective-taking was compared across three groups of children: (a) CD elevated on Callous-Unemotional traits (CD-high-CU, n = 30), (b) CD low on CU traits (CD-low-CU, n = 42), and (c) a 'typically-developing' comparison group (n = 50), matched in age (7.5 - 10.8), gender and socioeconomic background. Results The results revealed deficits in CD-low-CU children for both affective and cognitive perspective-taking. In contrast CD-high-CU children showed relative competency in cognitive, but deficits in affective-perspective taking, a finding that suggests an affective-specific defect and a plausible dissociation of affective and cognitive perspective-taking in CD-high-CU children. Conclusion Present findings indicate that deficits in cognitive perspective-taking that have long been implicated in CD appear to be characteristic of a subset of CD children. In contrast affective perspective-taking deficits characterise both CD subgroups, but these defects seem to be following diverse developmental paths that warrant further investigation.